2017
DOI: 10.1097/bot.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Implant Removal Following Dual Mini-Fragment Plating for Clavicular Shaft Fractures

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…On the contrary, higher patient cosmetic acceptability has been reported with small single plate fixation compared with larger, more prominent plates (95% vs 50%, respectively). Recently, excellent clinical outcomes, 100% union rate, and 0% reoperation rate have been reported with dual small plate fixation [7,10,11,[13][14][15][16]. This has caused clinical interest in dual small plating, to minimize hardware irritation and reoperation rates.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, higher patient cosmetic acceptability has been reported with small single plate fixation compared with larger, more prominent plates (95% vs 50%, respectively). Recently, excellent clinical outcomes, 100% union rate, and 0% reoperation rate have been reported with dual small plate fixation [7,10,11,[13][14][15][16]. This has caused clinical interest in dual small plating, to minimize hardware irritation and reoperation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is important to note that the primary impetus for using the dual-plating technique is not specifically to lessen implant removal. As noted by previous studies using dual plating, dual plating of the clavicle is advantageous for the reduction, maintenance of reduction, and fixation of complex fracture patterns 14 , 21 - 23 . Because of the retrospective nature of the study, the ASES Standardized Shoulder Assessment Form was unable to be administered to patients who required implant removal before their implants were removed.…”
Section: Discussionmentioning
confidence: 76%
“…Clinically, they reported 0 implant removals at 1 year of follow-up 14 . Another dual mini-fragment plating series, by Czajka et al, published in 2017, showed an all-cause reoperation rate of 7.4% 21 , which was slightly higher than that of Prasarn et al 14 , although still lower than published single-plate data.…”
Section: Discussionmentioning
confidence: 78%
“…All patients showed radiological healing of the fracture, and no further surgery was necessary [4]. In a larger series at the University of Houston, Texas with 81 patients treated with the identical technique, good functional results with a mean DASH score of 8.4 points were found at a median of 477 days postoperatively [5]. In one patient (1.2 %), there was an early loss of reduction during weight lifting 4 weeks postoperatively, necessitating revision of open reduction and internal fixation (ORIF).…”
Section: Claviclementioning
confidence: 84%